Study of stump flexion contracture towards postural stability for transtibial prosthesis users / Mohd Fazli Ghazali - Mohd Fazli, Ghazali (2018)
Knee flexion contracture on the residual limb, which is called as stump flexion contracture, is a condition which refers to the inability of the knee to move in the normal range of motion (ROM). In simpler words, the knee cannot be fully extended. It is one of the common problems occurring among the below-knee amputees. The main cause of this condition is the failure of the soft tissue, which is commonly the flexor muscles, to lengthen in tandem with the bone. This happens as a result of muscles shortening and stiffness due to long periods of bending position or inactivity caused by illness and lack of exercise. Stump contracture could bring several adverse effects to the amputees when using prostheses, such as limitation of the motion required for regular activities and functions. To overcome the effects, a prosthetist will setup the prosthetic alignment according to the ROM of the stump. However, there is still no specific study regarding the effect of prosthetic alignment accommodating the ROM of stump contracture. The current study had been carried out by using Biodex Stability System (BSS) in order to investigate the effect of stump flexion contracture towards the postural stability among the below-knee prosthesis users with the intervention of alignment accommodation. The BSS provides the reading of anterior-posterior stability index (APSI), medial-lateral stability index (MLSI), and overall stability index (OSI). A higher reading of the index indicates lesser stability. Each of the subjects had been tested in three different sessions which were Visit 1 (before contracture improvement), Visit 2 (after contracture improvement without alignment readjustment), and Visit 3 (after contracture improvement with alignment readjustment). The APSI reading was significantly higher during Visit 2 with p=0.007 and p<0.0001 compared to Visit 1 and Visit 3 respectively. The OSI during Visit 2 was also found to be significantly higher compared to Visit 3 (p<0.0001). It was increased by 47.5% after Visit 1 but had been proven insignificant by one-way ANOVA statistical test (p>0.05). In Visit 2, the degree of contracture was significantly improved (p<0.0001), which was 44.1% less than Visit 1. The stability index in anterior-posterior aspect (APSI) was proven to be lower as the prosthetic alignment was adjusted according to the ROM of the knee. This finding explains that the alignment set up based on the adaptation with the ROM of the stump can positively contribute in maintaining postural stability. With a significant number of subjects (n=10), the standard range of stability index also had been obtained for the amputee population who have similar characteristics.